Clinical and Hematological profile of Paediatric Patients with Cleft Lip and Palate in a Tertiary Care Hospital of Haryana, India - Richa, -; Sharma, Shashi; Madan, Sakshee; Singh, Sanasam Manimukta; Yadav, Bharti; Yadav, Daksh (Journal of Nepal Paediatric Society, 2021)
Introduction: Cleft lip and/ or cleft palate are the most common visible craniofacial anomalies. These patients often have feeding difficulties and recurrent infections leading to an altered immune system which can be assessed by the variations in hematological parameters. We intended to assess the clinical profile and the hematological parameters in patients with cleft lip and palate. Methods: This is a three-year cross-sectional study conducted at SGT Medical College, Gurugram, Haryana, India from January 2017 to December 2019 involving assessment of patients with cleft lip and palate who visited the paediatric unit for complete evaluation before surgery. Syndromic children or those with associated deformities were excluded .A total of 115 patients were enrolled in the study and the following information was recorded: Age, Gender and type of cleft (Cleft lip and alveolus, cleft lip, alveolus and palate, and isolated cleft palate). Hematological parameters including hemoglobin, total leukocyte count, differential leukocyte count, absolute eosinophil count, and red cell indices were evaluated and compared amongst the anatomical subtypes. Results: A total of 115 patients were included in the study, of which 66 (57.4%) were males and 49 (42.6%) were females. 57 (49.6%) had a cleft lip, alveolus, and palate, 36 (31.3%) had a cleft lip and alveolus and 22 (19.1%) had cleft palate only. Anaemia was present in 71.1% of cases. 83.4% cases of cleft lip and alveolus while81.8% of isolated cleft palate were anaemic. Microcytic hypochromic anaemia was present in 63.4% of cases while 36.6% had normocytic normochromic anaemia. The total leukocyte count was elevated in 60 children (52.2%) which was highest in cleft lip and alveolus (66%). Absolute neutrophil count was significantly high in the lip and alveolus groups.(13.9%) Absolute lymphocyte count was highest in lip and alveolus (30.56%). Absolute monocyte count and the absolute eosinophil count was low in the majority of cases. Conclusions: A large number of children with cleft lip and/ or palate are not exclusively breastfed due to anatomical deficits. They need supplemental iron to meet the demands. A standard policy to provide auxillary iron by health care professionals should be made at the first visit to the health centre because nutritional anaemia negatively affects the physical and cognitive development of a child. It also unnecessarily prolongs the date for optimum and safe surgery.